Kebijakan Investasi Di Beberapa Negara Asean (Suatu Komparasi) - Emiel Salim Siregar; Tiwi Agustiani; Maulidia Shella Devi; Salsabilah Nazwa; Nazwa Satria Arisandi (Jurnal Warta Dharmawangsa, 2026)
Investment policies in the ASEAN region play an important role in boosting economic growth, enhancing competitiveness, and strengthening regional cooperation among member countries. Investment development in ASEAN has experienced rapid growth due to support from stable economic growth, a large population, and a strategic geographical position. ASEAN countries implement various investment policies such as providing tax incentives, infrastructure development, bureaucratic simplification, and the development of modern industrial sectors to attract both domestic and foreign investors. Although sharing similar goals, each ASEAN country also has differences in policies according to their economic conditions and national development priorities. Singapore focuses more on the technology and financial services sectors, Indonesia on infrastructure and manufacturing, while Vietnam is prominent in the labor-based manufacturing sector. Investment policies It provides a positive impact on economic growth, job creation, technology transfer, and the improvement of human resource quality in the ASEAN region. However, there are several challenges such as global competition, infrastructure disparity, and global economic instability. Therefore, ASEAN countries need to continuously strengthen economic cooperation, improve the quality of regulations, and create economic stability so that investment prospects in the ASEAN region continue to grow and are able to compete at the international level